Personal Agency Features of Younger Adolescents with A High Degree Of Passion for Computer Games - Viktorovna Grishina, Anna; Nikolaevna Volkova, Elena (International Journal of Engineering and Technology, 2018)
In the era of intensive informatization of society, computer becomes an integral part of the modern life of the younger teenagers. In Russia, the number of children spending time in front of monitors, playing computer games at home or in a computer club, increases every day. According to Entermedia LLC, the percentage of sales of computer games increases by 50% annually. Currently, 23% of the population of Russia plays computer games, at that the minimum age for a computer player is two years.Strengthening polarization regarding children's interest to computer games becomes one of the most important problems. What is meant here is the fact that, on the one hand, there are adolescents, whose interest in computer games is quite sustainable, while, on the other hand, there are also schoolchildren experiencing mild interest or no interest at all to computer games. The relevance of the present work is determined by the social danger of the phenomenon called high passion for computer games, which deforms, and sometimes blocks the development of the most important personal entities [3, 5, 9, 12, 15]. In this regard, the investigation of the features of personal agency in younger adolescents, which is responsible for the self-regulation of behavior and activity of a subject, is of particular importance.Â